2018
DOI: 10.1111/fwb.13224
|View full text |Cite
|
Sign up to set email alerts
|

Stressor interactions in freshwater habitats: Effects of cold water exposure and food limitation on early‐life growth and upper thermal tolerance in white sturgeon, Acipenser transmontanus

Abstract: Limited food availability and altered thermal regimes (e.g. cold water releases from dams) are two common stressors threatening the persistence of fishes inhabiting anthropogenically disturbed freshwater systems. Yet, the combined effects of these stressors remain poorly characterised. To remedy this, we examined the isolated and combined effects of low temperature exposure and food restriction on specific growth rate (SGR, % body mass/day) and upper thermal tolerance (critical thermal maxima, CTMax) in larval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 84 publications
1
13
0
Order By: Relevance
“…The initiation timing of feeding was chosen to coincide with developmental milestones that may influence drift: olfactory development and initiation of exogenous feeding for larvae that develop at 14 • C (Dettlaff et al, 1993;Jay et al, 2020). Food rations were calculated using methods described in Rodgers et al (2018). Deng et al (2003) determined the optimal feeding rate for first-feeding larval white sturgeon is 26% body weight/day at 19.5 • C. Using the relationship between temperature and optimal feeding rate found by Cui and Hung (1995) for juvenile white sturgeon, optimal feeding rate decreases 54% between 19.5 and 14 were fed a commercial diet of frozen, enriched Artemia metanauplii (Hikari Bio-Pure).…”
Section: Methodsmentioning
confidence: 99%
“…The initiation timing of feeding was chosen to coincide with developmental milestones that may influence drift: olfactory development and initiation of exogenous feeding for larvae that develop at 14 • C (Dettlaff et al, 1993;Jay et al, 2020). Food rations were calculated using methods described in Rodgers et al (2018). Deng et al (2003) determined the optimal feeding rate for first-feeding larval white sturgeon is 26% body weight/day at 19.5 • C. Using the relationship between temperature and optimal feeding rate found by Cui and Hung (1995) for juvenile white sturgeon, optimal feeding rate decreases 54% between 19.5 and 14 were fed a commercial diet of frozen, enriched Artemia metanauplii (Hikari Bio-Pure).…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis by Bell et al (2009) found that several behavioural traits that were repeatable often differed among age classes, across sexes (also reported in O' Donnell et al 2020) and between field and laboratory studies. Many factors can elicit plasticity (variation) in CT max estimates, including differences in life stages (e.g., Illing et al, 2020;Recsetar et al, 2012), diet (Isaza et al, 2019), water quality (e.g., Ern et al, 2016;Potts, 2020;Sardella et al, 2008), habitat (Rodgers et al, 2019), reproductive stage (Auer et al, 2021;Dahlke et al 2020;Johnson, 1976;Wheeler et al, 2022) and social status (Gilmour & Bard, 2022;LeBlanc et al, 2011). Chronic stress in fish can also impair responses to thermal stress (e.g., Gilmour & Bard, 2022;Claireaux et al, 2013;LeBlanc et al, 2011).…”
Section: Is Ct Max Repeatable and What Does That Tell Us About Herita...mentioning
confidence: 99%
“…2020) and between field and laboratory studies. Many factors can elicit plasticity (variation) in CT max estimates, including differences in life stages ( e.g ., Illing et al ., 2020; Recsetar et al ., 2012), diet (Isaza et al ., 2019), water quality ( e.g ., Ern et al ., 2016; Potts, 2020; Sardella et al ., 2008), habitat (Rodgers et al ., 2019), reproductive stage (Auer et al ., 2021; Dahlke et al . 2020; Johnson, 1976; Wheeler et al ., 2022) and social status (Gilmour & Bard, 2022; LeBlanc et al ., 2011).…”
Section: Evaluating the Ecological Relevance Of Ctmax As A Measure Of...mentioning
confidence: 99%
“…For example, altered temperature regimes greatly increased mortality of larval and early juvenile life stages of razorback sucker, Xyrauchen texanus, flannelmouth sucker, Catostomus latipinnis, Humpback Chub, Gila cypha, and Colorado squawfish (pikeminnow), Ptychocheilus lucius (Clarkson and Childs 2000). Hence, changes to water temperatures are often a major stressor to riverine ecosystems and their biota (Dudgeon et al 2006;Rodgers et al 2019).…”
Section: Introductionmentioning
confidence: 99%